The lost city / Beijing - Alexander Street Press; Phoenix Satellite Television Limited (New York, NY : Filmakers Library, 1964)
This enlightening film looks at the issues of urban gentrification and preservation in Beijing today. For the past decade many of the city's old neighborhoods, the ancient, densely populated enclaves of narrow, winding streets and crumbling courtyard houses have been steadily demolished due to industrialization and modernization. The houses called "hutongs," were built around a central courtyard which provided structure for each family's development. Many were labelled unsafe by the government and have now been replaced by office towers and high-rise apartments.Much of the devastation has occurred in the Quianmen neighborhood, once the domain of the Qing dynasty (1644 -1911). For centuries it was filled with hutongs, opera halls and boarding houses filled with scholars. Quianmen is only one piece of the continuing citywide slum clearance and construction boom that have accelerated to prepare for the Olympic Games in 2008. Affordable housing has become such a serious problem that many people from old Beijing have been forced to the city's outskirts because they can no longer afford to live in their old neighborhoods. This has led to enormous traffic jams as more Chinese workers own cars and commute from the outskirts to the center. In 2005 the government came up with a new city plan which they hope will provide a way to accomodate both the city's heritage and its new development. This plan may provide for the city's growth as a world power center but has it come too late to save the city's architectural heritage?.
Originally released as DVD.
Title from resource description page (viewed May 24, 2011).
For College; Adult audiences.
Electronic reproduction.
English.
Keywords: City planning -- China -- Beijing; Gentrification -- China -- Beijing; Historic preservation -- China -- Beijing; Documentary